PENGARUH SOCIAL SKILL TRAINING (SST) TERHADAP KETERAMPILAN SOSIAL: KEBIASAAN POSITIF REMAJA TUNARUNGU KLASIFIKASI RINGAN DI SLB N I BANTUL YOGYAKARTA - Muryadi, Yokhanan; Isdiana, Laurentia Ajeng; Intening, Vivi Retno (STIKES Bethesda Yakkum, 2017)
Background: Physical barriers possessed by deaf chlirden can affect their psychological and social development. They will have difficulty in communicating with others, and it is difficult to express their mood. It causes these children to prefer to be alone. Objective: To determine the effect of SST on deaf adolesent socialization skills in SLB N I Bantul. Methods: This study used Quasi-Experimental design with one group pre-test and post-testdesign. Results: The of averaged increase socialization skills was 2,00%. The survey results revealed a significant difference score of social skills deaf adolesent before and after therapy. Conclusion: SST can be used as a medium for forming Characteristics and social interactions. Suggestion: Can be on input for SLB N I Bantul, to increase social therapy social therapy for the students.